2019
DOI: 10.3390/su11174639
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Measuring Fair Labour Justice in Hotels: Design for the Spanish Case

Abstract: There is a growing awareness of Corporate Social Responsibility (CSR) and sustainability as a global movement. The hospitality sector is one of the major industries driving socioeconomic development worldwide (especially in economies such as Spain) and it has responded to this need, in the context of a general worsening of labor conditions in this sector. Evidence of this response is the Fair Hotels Project, which is an international collaborative effort aimed at building new partnerships between fair trade mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(41 reference statements)
0
8
0
2
Order By: Relevance
“…In this way, we categorized the antecedents into three groups, including external, firm-level, and individual-level factors. Concerning external factors, previous studies mentioned different items that could have an impact on the SRHRM practices, such as laws and regulations [21,62,66,100], public demand and expectations [61,64,92], market pressures induced by, for example, competitors and/or customers [26,53,74], union pressures such as those coming from the International Labour Organization (ILO) [48,62,66], the national institutional context [78,89], and external crisis, such as what all organizations experienced due to the COVID-19 pandemic since its appearance in 2019 [72,76]. The second group of antecedents pertains to the firm-level factors.…”
Section: Antecedents Of Srhrmmentioning
confidence: 99%
See 3 more Smart Citations
“…In this way, we categorized the antecedents into three groups, including external, firm-level, and individual-level factors. Concerning external factors, previous studies mentioned different items that could have an impact on the SRHRM practices, such as laws and regulations [21,62,66,100], public demand and expectations [61,64,92], market pressures induced by, for example, competitors and/or customers [26,53,74], union pressures such as those coming from the International Labour Organization (ILO) [48,62,66], the national institutional context [78,89], and external crisis, such as what all organizations experienced due to the COVID-19 pandemic since its appearance in 2019 [72,76]. The second group of antecedents pertains to the firm-level factors.…”
Section: Antecedents Of Srhrmmentioning
confidence: 99%
“…As most of the studies in the reviewed papers were conducted by applying quantitative methods, as shown in Table 3, they more or less employed the same framework developed by Shen and Benson [94], Shen and Jiuhua Zhu [21], and Orlitzky and Swanson [20]. SRHRM practices were mostly adapted from the traditional HRM functions (i.e., recruitment and selection, training and development, working conditions, appraisal and reward) by including ethical and fairness issues such as the consideration of work-life balance through, for example, flexible working time (e.g., [63]), enhanced communication at work (e.g., [62]), safety and health at work (e.g., [49]), transparent criteria in recruitment and selection (e.g., [54]), equal opportunities (e.g., [53]), fair appraisal processes (e.g., [78]), training opportunities and different personal development alternatives such as employee participation in decision-making (e.g., [86]), as well as providing additional support for employee education [83]. However, some studies that emphasize specific practices, less addressed by previously structured frameworks, are worth mentioning.…”
Section: Practices In Srhrmmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the tourism sector generated 10.4% of global GDP, positioning as the second largest industry worldwide. In the last five years, this industry has emerged as one of the main drivers of socio-economic development, creating one in five new jobs [1,2]. In this context, Spain was one of the most established and popular Sustainability 2021, 13, 10710 2 of 24 tourist destinations internationally, with great importance of the hotel industry, although with low-quality employment in general terms [3].…”
Section: Introductionmentioning
confidence: 99%